(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Entrepreneurship plays a major role in developing society of a fast developing country like India. Entrepreneurs are agents who perform a vital role in the economic development of a country and are linked to the overall industrial development of a nation. The traditional roles of house wives are slowly but surely changing into women capacity and willingness to develop, organize, and manage a business along with any of its risks in order to make a profit entrepreneur. In view of the above an attempt has been made to study the influence of the motivational factors on Entrepreneurial Socialisation among women entrepreneurs in Tirunelveli. For the present study the data was collected from 50 women entrepreneurs in Tirunelveli.